Oscillibacter ruminantium sp nov., isolated from the rumen of Korean native cattle - Lee, Geun-Hye; Rhee, Moon-Soo; Chang, Dong-Ho; Lee, Jonghwan; Kim, Seil; Yoon, Min Ho; Kim, Byoung-Chan (MICROBIOLOGY SOC, 2013)
A strictly anaerobic, Gram-negative, non-spore-forming bacterium, designated GH1(T), was isolated from the rumen of Korean native cattle (HanWoo). Cells were straight to slightly curved rods (2.0-4.5 mu m long) and were motile by peritrichous flagella. The isolate grew at 30-45 degrees C (optimum 40 degrees C), at pH 5.5-6.5 (optimum pH 6.0) and with up to 3.5% (w/v) NaCl. Strain GH1(T) produced acid from D-glucose, D-ribose and D-xylose, with butyric acid being the major end product. The genomic DNA G+C content was 54.6 mol%. Based on comparative 16S rRNA gene sequence analysis, strain GH1(T) was most closely related to Oscillibacter valericigenes Sjm18-20(T) (97.3 % 16S rRNA gene sequence similarity). DNA-DNA hybridization between strain GH1(T) and O. valericigenes DSM 18026(T) showed 24% reassociation. The major fatty acids were iso-C-13:0 (13.0 %), iso-C-15:0 (17.6 %), anteiso-C-15:0 (8.4 %) and C-14:0 (4.1 %), and the cellular fatty acid methyl esters as dimethylacetals (DMAs) were C-16:0 DMA (17.8%), iso-C-15:0 DMA (15.2%) and C-14:0 DMA (4.52%). The cell-wall peptidoglycan of strain GH1(T) contained meso-diaminopimelic acid and the major cell-wall sugar was galactose. Based on 16S rRNA gene sequence similarity, phylogenetic analysis, DNA G+C content, DNA-DNA relatedness and distinct phenotypic characteristics, strain GH1(T) is classified in the genus Oscillibacter as a member of a novel species, for which the name Oscillibacter ruminantium sp. nov. is proposed. The type strain is GH1(T) (=KCTC 15176(T)=NBRC 108824(T)=JCM 18333(T)).